Swamp Forage Silage Organic Acid Profiles and Influence of Silage Liquid Organic Acid Salts Against Pathogenic Bacteria In vitro - Sandi , Sofia; Yosi, Fitra; Sari, Meisji Liana; Gofar, Nuni; Rofiq, Muhamad Nasir (International Journal of Poultry Science, 2020)
Background and Objective: Swamp forages are a potentially good quality poultry feed source and organic acids produced by fermentation determine the quality of the silage as a dietary source. This study was conducted to determine the organic acid profile in swamp forage silage and the effect of silage liquid organic acid salts on pathogenic bacteria drag zones. Materials and Methods: A completely randomized design was used consisting of threes wamp forage silage treatment groups with five replications: P1 (100% Hymenachne acutigluma), P2 (50%:50% H. acutigluma: Neptunia oleracea Lour) and P3 (100% N. oleracea Lour). The silage with the best organic acid profile was then reacted with NaOH (pH 10-12), Ca(OH)2 (pH 4.6-4.8) and ZnO (pH 4.6-4.8) to produce organic acid salts. Total lactic acid bacteria, acidity (total amount and pH), organic acidprofiles (lactic, acetic and butyric acid), total organic acid salt and pathogenic bacteria (Escherichia coli and Salmonella typhimurium) in drag zones after in vitro treatment with organic acid salt extracts were measured. Results: P1 silage had the highest total lactic acid bacteria, total acid and lactic acid content (p<0.05) and lowest butyric acid levels (p>0.05). Though not significantly different between treatments, acetic and butyric acid levels of all silages exceeded standards for good quality. Addition of ZnO to P1 silage liquid produced the most organic acid salt (p<0.05 versus NaOH) with the lowest pH (p<0.05 versus NaOH and Ca(OH)2]. ZnO-derived organic acid salt extracts produced the largest drag zone (greatest growth inhibition) for both E. coli [p<0.05 versus NaOH and Ca(OH)2] and S. Typhimurium (p<0.05 versus NaOH), while NaOH produced the smallest. Conclusion: Hymenachne acutigluma (P1) swamp silage had the best organic acid profile due to a higher amount of active lactic acid bacteria. Furthermore, addition of 12.5% ZnO to P1 silage liquid resulted in organic salt with the lowest pH and optimal inhibition of E. coli and S. typhimurium growth. These results indicate that Hymenachne swamp forage silage can be used as an alternative feed additive (organic acid salt) which is good for poultry.